0066 A Mexican Spanish Version of the Assessment of Sleep Environment. (25th May 2022) - Valencia, Dora; Begay, Tommy; Granados, Karla; Delgadillo, Marcos; Ghani, Sadia; Molina, Patricia; Alfonso-Miller, Pamela; Wills, Chloe; Grandner, Michael
Abstract: Introduction: Sleep research that has been previously completed with individuals of Mexican descent generally do not use instruments that have been translated in accordance with the language norms of the target community. In this study, the Assessment of Sleep Environment (ASE) was translated by a bilingual research study team. The ASE was then completed by English and Spanish speaking participants, in their preferred language. Methods: Data were collected from a sample of N=100 individuals of Mexican descent in Nogales, Arizona, located at the US-Mexico border. The ASE is a 13-item scale that quantifies the degree to which an individual perceives that their physical environment interferes with their sleep quality. It includes items about heat, cold, noise, quiet, light, dark, smell, humidity, comfort of sleeping surface and bedding, and safety. To translate the measure into Spanish, the following procedure was followed: (1) a bilingual study team member performed an initial translation; (2) a bilingual community member edited the translation; (3) a certified medical translator edited the revision; (4) a focus group of N=5 bilingual community members made contextual edits; (5) a back-translation was performed; (6) an additional bilingual focus group examined the final version for compatibility; and (7) the medical translator certified the accuracy of the final version. T-tests examined differences between those who completed the measure in Spanish vs English. Results: Of the N=100 survey respondents, N=42 completed the ASE in Spanish. No significant differences were seen in overall scores between those who completed the measure in English or Spanish (p=0.17). In addition, no differences were seen for individual items assessing light (p=0.19), dark (p=0.21), noise (p=0.73), quiet (p=0.15), heat (p=0.08), cold (p=0.96), pillows (p=0.93), firmness (p=0.98), other sleeping surface issues (p=0.08), or safety (p=0.28), but mean differences were seen for humid (0.04), smell (0.04), and softness (p=0.02), with respondents to the Spanish version reporting a lower degree of disturbance due to these factors. Conclusion: There were no significant differences seen in overall scores between those that completed the English and Spanish versions. Future studies can use the Spanish version of the ASE when assessing this population. Support (If Any):